Exploring the Potential of Blockchain Technology in Digital Tax Administration to Enhance Tax Compliance - Yenni Mangoting; Retnaningtyas Widuri; Dean Charlos Padji Dogi; Rosalia Gabronino (Institute of Research and Community Outreach - Petra Christian University, 2024)
This research seeks to enhance the technology acceptance model (TAM) by examining cognitive belief factors, specifically the influence of perceived usefulness and perceived ease of use, on taxpayers' intentions to utilize blockchain technology. This investigation explores both the direct and indirect effects of perceived enjoyment. This research also examined the impact of behaviour, specifically the trust factor, on perceived usefulness and perceived ease of use. We extended the TAM by assessing the mediating influences of the perceived enjoyment factor. The research employs a survey methodology. We collected data from 213 individual taxpayers. However, we were only able to process the data of 155 respondents. Questionnaires serve as a valuable tool for gathering data through Google Forms. We analysed the data using PLS-SEM. The research findings indicate that there is a form of mediation where the perceived usefulness of blockchain technology has a notable impact on taxpayers' intentions to use it, either directly or through the perceived enjoyment it brings. Perceived enjoyment also mediates the influence of perceived ease of use on taxpayers' intentions to use blockchain. Moreover, taxpayer trust has effectively influenced taxpayers' perceptions that technology is user-friendly and advantageous. To improve the level of service provided to taxpayers, tax authorities must leverage the advancements of the information technology era. The research findings make a valuable contribution to the tax authorities' readiness to adopt a blockchain-based tax administration system. The results highlight the significance of the authority's efforts to enhance taxpayers' intrinsic motivation when using tax information technology. Creating a user-friendly and enjoyable experience that brings joy, excitement, and comfort can achieve this.